Plant response to disturbance in a Mediterranean grassland: How many functional groups? - Lavorel, S; McIntyre, S; Grigulis, K (Journal of Vegetation Science, 2009)
. Data referring to changes in vegetation composition resulting from cattle exclosure and ploughing in a Portuguese pasture dominated by annuals were used to test hypotheses regarding the biology of species favoured or eliminated by disturbance in semi-natural herbaceous communities. These hypotheses were tested in two ways. First we compared the distribution of six a priori groups – grasses, small rosettes, large rosettes, small species with leafy stems, large species with leafy stems, legumes – across grazed, ploughed and undisturbed plots. In a second set of analyses we examined changes in the frequencies of individual biological attributes in response to grazing and ploughing. These analyses were carried out separately for grasses and dicot forbs. Overall, the species composition showed little response to either grazing or ploughing, though species dominance changed. This lack of responsiveness of species composition was attributed to the long history of intensive land use which has resulted in the loss of disturbance-intolerant species over entire landscapes. When considering a priori groups, small rosettes were indifferent to disturbance. grazing and ploughing showed that dominated. Large rosettes, large species with leafy stems and legumes were generally intolerant to both grazing and ploughing, though individual species may increase in response to disturbance. Small species with leafy stems were the only group favoured by grazing whereas ploughing favoured grasses. As to individual traits, grazing excluded large grass species with heavy seeds and promoted a flat rosette canopy structure and a small size, along with a moderate dormancy and protected inflorescences. In forbs, grazing favoured small species, as expected, while it excluded tall species, and, in contrast to earlier results, a rosette canopy. These attributes were consistent with responses of the a priori groups, though it would not have been possible to reconstruct groups directly from the attribute list. Ploughing had no effect on any of the forb traits. As to grass traits, flat- and short-statured species increased and heavy-seeded species decreased. Our analysis revealed two advantages of establishing plant functional classifications within life forms. Subgroups within forbs had contrasting types of behaviour. For the same trait patterns could differ within the grass group from within the forb group. Finally, this analysis emphasizes the need for plant functional classifications aiming at the identification of syndromes of co-occurring attributes rather than of lists of isolated traits of which actual combinations are not specified.
Keywords: Annual; disturbance; Grazing; Plant functional type; Ploughing; Portugal